Comparative investigation of Rheum tataricum and Rheum palmatum - Minkayeva, A.A.; Azilbek, L.; Amzeyeva, U.; Karunakaran, T.; Liu, X.; Shang, X.; Muzaffarova, N.; Jenis, J. (International Journal of Biology and Chemistry, 2025)
Medicinal plants have played a crucial role in both traditional and modern medicine for centuries. Among these, Rheum tataricum and Rheum palmatum have attracted significant attention due to their diverse pharmacological properties and rich chemical compositions. Despite their widespread use, detailed comparative studies of these species remain limited. This study aims to provide a comprehensive evaluation of their morphological characteristics, chemical profiles, and pharmacological effects to enhance their application in medicine and drug development. The study involved the identification of liposoluble constituents in R. tataricum and R. palmatum using Gas Chromatography-Mass Spectrometry (GC-MS). The chemical compositions of both species were investigated, and their bioactive compounds were quantified. The pharmacological significance of key compounds such as oleic acid, hexadecanoic acid, octadecadienoic acid, chrysophanol, and apocynin was evaluated based on existing literature. GC-MS analysis revealed distinct differences in the chemical compositions of R. tataricum and R. palmatum. The Chinese species, R. palmatum, contained twenty-four compounds, with oleic acid (53.9±0.09%) as a predominant constituent. In contrast, R. tataricum from Kazakhstan contained eighteen compounds, with a notably higher content of chrysophanol (35.1±0.05%). Hexadecanoic acid (18.9%) was found to be a major component in both species, demonstrating moderate antibacterial activity. Other bioactive compounds such as octadecadienoic acid, 9,10-anthracenedione, apocynin, and orcinol were detected, indicating their potential therapeutic applications. This comparative study provides valuable insight into the chemical compositions and pharmacological relevance of R. tataricum and R. palmatum. The significant variation in bioactive compound concentrations suggests distinct therapeutic potentials. These findings support the rational use of these medicinal plants in pharmaceutical applications and highlight their relevance in both drug discovery and traditional medicine practices. Keywords: Medicinal plants, Rheum tataricum, Rheum palmatum, phytochemical content, GC-MS.